A data mining and semantic analysis reveals novel insights into the genetic characteristics of the glucocorticoid receptor interactome. (2023) - Sigala, Markezina; Mitsis, Thanasis; Papageorgiou, Louis; Papakonstantinou, Eleni; Diakou, Io; Pierouli, Katerina
No abstract available